2022
DOI: 10.1093/geroni/igac059.2480
|View full text |Cite
|
Sign up to set email alerts
|

Changes to Care Provisions to Older Adults During Covid-19: Implications for Caregiver Well-Being

Abstract: Among the many consequences of the COVID-19 pandemic is its impact on caregiving for older adults. Pandemic-related physical distancing policies, avoidance of infection risk, and changing obligations at home and work has caused shifts in care that may not have occurred otherwise. We use nationally representative data on 2,363 caregivers to older family members and friends collected at the height of the pandemic to explore the extent to which family caregivers changed the amount and types of care they provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[655][656][657][658][659][660][661][662][663][664][665] Fatigue and burnout among dementia caregivers and their lack of access to services and supports for themselves and for the people for whom they provide care are common themes in research on the wide-ranging effects of the COVID-19 pandemic. 666 For these reasons, the pandemic has created a crisis for dementia caregivers. 655,667,668 Telephone interviews with family caregivers in rural Virginia following the governor's stay-at-home order in 2020 found that those who were more concerned about the COVID-19 pandemic and those who received less help from family and friends experienced greater feelings of emotional exhaustion and fatigue related to dementia care.…”
Section: Covid-19 and Dementia Caregivingmentioning
confidence: 99%
See 2 more Smart Citations
“…[655][656][657][658][659][660][661][662][663][664][665] Fatigue and burnout among dementia caregivers and their lack of access to services and supports for themselves and for the people for whom they provide care are common themes in research on the wide-ranging effects of the COVID-19 pandemic. 666 For these reasons, the pandemic has created a crisis for dementia caregivers. 655,667,668 Telephone interviews with family caregivers in rural Virginia following the governor's stay-at-home order in 2020 found that those who were more concerned about the COVID-19 pandemic and those who received less help from family and friends experienced greater feelings of emotional exhaustion and fatigue related to dementia care.…”
Section: Covid-19 and Dementia Caregivingmentioning
confidence: 99%
“…Existing reports indicate that the COVID‐19 pandemic has posed significant social, psychological, emotional and physical challenges to family members and friends who provide care for people with dementia 655–665 . Fatigue and burnout among dementia caregivers and their lack of access to services and supports for themselves and for the people for whom they provide care are common themes in research on the wide‐ranging effects of the COVID‐19 pandemic 666 . For these reasons, the pandemic has created a crisis for dementia caregivers 655,667,668 …”
Section: Caregivingmentioning
confidence: 99%
See 1 more Smart Citation